2015
DOI: 10.2174/0929867322666150114151248
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function of Prokaryotic UDP-Glucose Pyrophosphorylase, A Drug Target Candidate

Abstract: UDP-glucose is an essential metabolite for a variety of processes in the cell physiology in all organisms. In prokaryotes, it is involved in the synthesis of trehalose, an osmoprotectant, in galactose utilization via the Leloir pathway and it plays a key role in the synthesis of the components of the bacterial envelope, particularly the lipopolysaccharide and the capsule, which represent necessary virulence factors of many bacterial pathogens. UDP-glucose is synthesized in bacteria by the prokaryotic UDP-gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 73 publications
1
55
0
Order By: Relevance
“…One of the most distinctive roles of UDP-Glc and derived nucleotide sugars is the biosynthesis of polysaccharides and glycoconjugates forming the cell surface coat. In bacteria, UGP controls the biosynthesis of the most important virulence factors and is valued as antibacterial target since it is frequently essential for pathogenicity or growth [ 27 ]. Similarly, in the trypanosomatid parasites Trypanosoma brucei and Trypanosoma cruzi , which are closely related to Leishmania , biosynthesis of UDP-Glc is essential for parasite growth.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most distinctive roles of UDP-Glc and derived nucleotide sugars is the biosynthesis of polysaccharides and glycoconjugates forming the cell surface coat. In bacteria, UGP controls the biosynthesis of the most important virulence factors and is valued as antibacterial target since it is frequently essential for pathogenicity or growth [ 27 ]. Similarly, in the trypanosomatid parasites Trypanosoma brucei and Trypanosoma cruzi , which are closely related to Leishmania , biosynthesis of UDP-Glc is essential for parasite growth.…”
Section: Discussionmentioning
confidence: 99%
“…observed for other bacterial UGPs [ Fig. 1(a)] (Berbís et al, 2015;Thoden & Holden, 2007a). Each chain in the tetramer is structurally very similar to the others, with aligned r.m.s.d values ranging from 0.2 to 0.4 Å .…”
Section: Resultsmentioning
confidence: 58%
“…Structural studies using X-ray crystallography have revealed that many of these bacterial UGPs share a very similar three-dimensional structure in which the enzyme crystallizes as a tetramer, with each monomer consisting of a central mixed -sheet that is surrounded by -helices (Berbís et al, 2015). Efforts to screen for inhibitors of S. pneumoniae UGP identified a functional assay that has yielded initial compounds that display inhibitory activity, but to date no other inhibitors of bacterial UGPs have been reported (Zavala et al, 2017;Berbís et al, 2015). Here, we describe the first crystal structure of UGP from Y. pestis, which may be useful in efforts to develop inhibitors of this enzyme.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The capsule synthesis regulator rcsB is implicated in the activation of ftsZ which is involved in forming the cell division apparatus in E. coli (Gervais et al ., ; Carballès et al ., ), and this might yield higher growth rates. Furthermore, the capsule core gene product GalF via its interaction with GalU, leads to increased cellular levels of uridine diphosphate (UDP)–glucose (Marolda and Valvano, ), which is a precursor for carbohydrate biosynthesis and hence may lead to the production of energy (Marolda and Valvano, ; Berbís et al ., ; Ebrecht et al ., ). Structurally, the Klebsiella capsule is thicker (160 nm) than the E. coli K1 capsule which is less than 10 nm in thickness, and the Klebsiella capsule has a denser arrangement of fine fibres compared with the E. coli K1 capsule (Amako et al ., ).…”
Section: Discussionmentioning
confidence: 98%